Sexual Exploitation: Professionals’ and Stakeholders’ Perceptions of Prevention, Assistance, and Protection for Victims in Portugal - Marlene Matos; Jacinta Sousa; Sónia Caridade; Isabel Dias (Social Sciences)
Sexual exploitation is a pervasive issue affecting individuals globally, characterized by the abuse of vulnerability, power, or trust for sexual purposes. This study aims to explore the perceptions of professionals and stakeholders in Portugal regarding the prevention, assistance, and protection of victims of sexual exploitation. Employing a qualitative research approach, four online focus groups were conducted with 17 participants from various professional backgrounds. The results highlight a comprehensive understanding of sexual exploitation among participants, who emphasized the coercion and exploitation of vulnerabilities as central elements. Significant barriers to addressing sexual exploitation were reported, including underreporting, societal indifference, and the impact of new technologies. Participants called for enhanced training for professionals across sectors, increased societal awareness, and stronger legal and policy frameworks. The study concludes with recommendations for elevating sexual exploitation as a governmental priority, improving professional training, and fostering international cooperation to combat this complex issue effectively.